Digital Cultural Fusion: The Transformation of Influencers and Social Media Marketing in Shaping The New Cultural Marketing Identity Coffee Shops - Ari Prabowo; Paningkat Siburian; Rosita Bangun (Journal of Business Management, 2025)
Indonesia is one of the world's leading coffee producers, and most of its Arabica coffee plantations are located in North Sumatra. The coffee trend in Indonesia has now also penetrated into concepts that were previously unimaginable. Many coffee shops no longer prioritize the taste of coffee but instead focus on ambiance. The purpose of this research is to know and analyze the influence of influencer marketing and social media marketing partially and simultaneously on new cultural marketing to coffee shop consumers in Medan City. The method used in this research uses a method, namely the type of research used in this research is a quantitative research method. This research uses an analytical tool is SPSS Version 23. The population in this study was all coffee shop consumers in Medan City, whose number could not be determined with certainty. The sampling method in this study uses accidental sampling technique. The sampling method in this study uses accidental sampling technique. By using the Lameshow formula, the final sample size used was 100 people. The results of this research are (1) Influencer marketing partially has a positive and significant effect on new cultural marketing, (2) Social media marketing partially has a positive and significant effect on new cultural marketing, (3) Influencer marketing and social media marketing together or simultaneously have a positive effect and significant to the new cultural marketing